Review for the generalist: evaluation of low back pain in children and adolescents - Houghton Kristin M (BMC, 2010)
Abstract Back pain is common in children and adolescents. Most cases of back pain are non-specific and self-limiting. In children and adolescents, pain is usually related to the posterior elements of the spine and disc-related problems are rare. Serious pathology, including malignancy and infection needs to be excluded. Evaluation and management is challenging and requires a thorough history and physical exam, and understanding of the immature skeleton. Diagnostic imaging is useful in the evaluation of a child or adolescent with low back pain and can help guide management. This article will review common causes of back pain in the pediatric population.